Pembuatan Hand Sanitizer dari Ekstrak Daun Salam (Syzygium polyanthum) Sebagai Alternatif Pembersih Tangan Bebas Alkohol - Sari, Nirmala; Fajriani, Fajriani; Nila, Ida Ratna (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2021)
Hand sanitizer products on the market generally contain alcohol which can cause dry hands and dehydration of the skin, therefore alternative ingredients that are skin-friendly and do not irritate the skin are needed such as the use of natural ingredients. One of them is bay leaf (Syzygium polyanthum). Salam plant is a plant that has antibacterial properties. The main ingredients that have antibacterial properties are flavonoids, tannins, essential oils, steroids, so that bay leaves can be used as a hand sanitizer to reduce alcohol use. The manufacture of bay leaf hand sanitizer is done by extracting the bay leaves with 96% ethanol solvent. The extraction results are then dissolved with other supporting materials which are certainly safe for health. It is hoped that the bay leaf hand sanitizer will be a safer alternative to hand sanitizers than alcohol-based hand sanitizers